Chronic venous insufficiency – an update. Part I – pathomechanism, sings, diagnostics - Żmudzińska, Maria; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
This paper is the first part of the articles series concerning chronic venous insufficiency (CVI). CVI is known as a problem of both medical and social character. It affects a significant percentage of European population and the growing prevalence of CVI is observed over the last years. Complex pathophysiological processes, which take place in the course of CVI lead to development of characteristic clinical signs. Modern, noninvasive diagnostic methods enable detailed determination of observed disorders. Disturbances in the low extremities venous blood flow lead to venous hypertension. White cell trapping, fibrin cuff and blood hyperviscosity theories are known as the most important hypotheses explaining the development of CVI. Commonly used CVI classifications enable to present both varied pathophysiological mechanisms and clinical signs in the standardized way. The modern CVI diagnostics is based on the non-invasive, painless and safe methods.